2011
DOI: 10.1007/s13277-011-0195-0
|View full text |Cite
|
Sign up to set email alerts
|

The nucleosome binding protein NSBP1 is highly expressed in human bladder cancer and promotes the proliferation and invasion of bladder cancer cells

Abstract: NSBP1 is a recently identified member of the HMGN protein family which binds to nucleosomes and regulates gene transcription through chromatin remodeling. In this study, we aimed to investigate the potential role of NSBP1 in human bladder cancer. We examined NSBP1 expression in 114 surgically removed bladder cancer specimens as well as 11 human bladder cell lines by immunohistochemistry and Western blot analysis, and found that NSBP1 level was correlated with the increased tumor grade and pathologic stage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…In bladder cancer, high HMGN5 expression is positively correlated with the tumor grade and lymph node metastasis, and HMGN5 silencing suppresses cancer cell proliferation and invasion (Wahafu et al, 2011). Consistently, Ji et al (2012) reported that HMGN5 is strongly expressed in clear cell renal cell carcinoma tissues that were correlated with the tumor grade.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In bladder cancer, high HMGN5 expression is positively correlated with the tumor grade and lymph node metastasis, and HMGN5 silencing suppresses cancer cell proliferation and invasion (Wahafu et al, 2011). Consistently, Ji et al (2012) reported that HMGN5 is strongly expressed in clear cell renal cell carcinoma tissues that were correlated with the tumor grade.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, MMP9 promotes tumor metastasis by enhancing the cell invasion ability of tumor cells (Belotti et al, 2003). Previous studies reported that HMGN5 inhibition can impair the expressions of cyclin B1, Bcl-2, and MMP9 ( Jiang et al, 2010;Wahafu et al, 2011;Ji et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Protein concentration was measured using BCA Protein Assay Kit (CWBIO, China), and equal amounts of protein (20 μg) were separated in 12 % sodium dodecylsulfate (SDS)-polyacrylamide gels. Western blot analysis was performed according to a standard protocol as described previously [20]. The primary antibodies used in this study contained: anti-Flag, caspase9, caspase8, P53, Bcl-2, Bcl-xl, Bax, cleaved caspase 3, PARP, tubulin (Cell Signal Tech, USA), GAPDH, caspase3 (Protein Tech, USA), and KCNJ1 (Sigma, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The expression of HMGN5 protein varies significantly between cells and tissues during embryonic development (Shirakawa et al, 2000). In addition, HMGN5 expression is upregulated with the development of several cancers, including squamous cell carcinoma, breast and bladder cancer, renal cell carcinoma, and gliomas (Gerlitz, 2010; Ji et al, 2012b; Li et al, 2006a; Qu et al, 2011; Tang et al, 2008b; Wahafu et al, 2011). Knockout of HMGN5 by RNAi inhibits cell proliferation and increases apoptosis in cancer cells (Chen et al, 2012b; Ji et al, 2012b; Zhang et al, 2012c).…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%